Priming with growth regulators stimulates germination, growth and physiological characteristics of Indian squash (Praecitrullus fistulosus) - Qamar, Rafi; Khan, Sanaullah; Safdar, Muhammad Ehsan; Rehman, Abdul; Atique-ur-Rehman; Javeed, Hafiz Muhammad Rashad; Khan, Bilal Ahmad (Journal of Pure and Applied Agriculture, 2023)
Indian squash (Praecitrullus fistulosus) is a summer vegetable crop in which higher temperature limits its production during sowing period. The present experiment 1 and 2 elucidated the possible effect of plant growth regulators on germination, growth and physiological characteristics of Indian squash (cv. Sahavi) under laboratory conditions. A completely randomized design with fourteen treatments (non-primed dry seeds (control), priming with distilled water, indole acetic acid @ 100, 150, 200 mg L-1 , salicylic acid @ 50, 100, 150 mg L-1 , ascorbic acid @ 50, 100, 150 mg L-1 and thiourea @ 500, 1000, 1500 mg L1 ) was used. Results of experiment 1 and 2 indicated that priming treatment of ascorbic acid @ 100 mg L-1 significantly (P ≤ 0.05) improved germination (93 and 94%) and seedling vigor index (1515.4 and 1531.2). Moreover, ascorbic acid @ 100 mg L -1 produced heavier shoot (2012.5 and 2014.1 mg) and root (424.7 and 425.4 mg) fresh weight and longer shoot (8.58 and 8.61 cm) and root (7.65 and 7.67 cm) length per seedling. Furthermore, results depicted that ascorbic acid @ 100 mg L1 enhanced photosynthesis (3.72 µmol m-2 s -1 ), chlorophyll (30.98 and 30.99 SPAD), total soluble proteins (1.53 and 1.54 mg g1 F. wt.), proline (7.94 and 7.95 µmol g-1 f. wt.), rate of transpiration (3.30 and 3.32 mmol m -2 s -1 ) and stomatal conductance (3.90 and 3.91 mmol m-2 s -1 ) during experiment 1 and 2. Additionally, ascorbic acid @ 100 mg L-1 was shortened in time to 50% germination (2.99 and 3.00 days) and mean germination time (3.00 and 3.03 days). It is concluded that a low dose of ascorbic acid @ 100 mg L-1 followed by salicylic acid @ 50 mg L-1 can effectively improve the germination characteristics, growth and physiological attributes of Indian squash. © 2021 Department of Agricultural Sciences, AIOU